Do investors follow the herd in option markets? - Bernales, Alejandro; Verousis, Thanos; Voukelatos, Nikolaos (Journal of Banking & Finance, 2020)
We investigate the previously unexplored herding behaviour of investors in option markets, by examining equity option contracts traded in the US between 1996 and 2012. We document strong herding effects in option trading activity that are conditional on a set of systematic factors related to periods of market stress. More specifically, we find that option investors tend to herd during periods of high market volatility risk, on dates of macroeconomic announcements, during the financial crisis of 2008, when a large number of market option positions is either opened or closed, and during periods of a large average dispersion of analysts’ forecasts.